The Figurative and Doctrinary Display of Walter Benjamin’s Philosophical Writing - Hernández Gutiérrez, Luis Eduardo (Resonancias. Revista de Filosofía, 2021)
This research aims to show the connection of Benjamin’s cognitive theory [Erkenntnistheorie] around a series of theological categories, deployed from the concept of doctrine [Lehre], assuming the updating of an original philosophical practice that was based on truth and in exposing a few ideas. From a singular figuration of knowledge that is based on language, a writing that is recognized in poetic and literary tropes is promoted, assuming the importance of the reflective and critical relationship in the work of art. Philosophical writing is presented as a singular figuration that wants to recover an experience of the remembrance thinking, which can redeem and save from oblivion, especially from a historical configuration of the present as an instant of readability, allowing a superior update, as long as it is connected with to the categories of politics and historiography.